Root cause analysis of accidents and examining their interrelations from the perspective of workers, supervisors, and safety officers - Neda Molamehdizadeh; Gholam Hossein Halvani; Hossein Ebrahimi; Ali Asghar Farshad; Seyedeh Melika Kharghani Moghadam; Tahereh Eskandari (PLoS ONE, 2025)
Identifying the root causes of accidents and analyzing their causal relationships is a fundamental step in designing effective preventive strategies. This study aimed to uncover the root causes of mining accidents and determine the interactions among them from the perspectives of workers, supervisors, and safety officers using a mixed qualitative-quantitative approach and the fuzzy DEMATEL method. The study was designed as a mixed-method approach (qualitative-quantitative). In the qualitative phase, a total of 69 interviews were conducted (23 with workers, 21 with supervisors, and 25 with safety officers) to identify and categorize the root causes of accidents. In the quantitative phase, 33 participants (11 from each group) took part in expert panels where the fuzzy DEMATEL method was employed to analyze the relationships among the factors. The qualitative phase results revealed that workers primarily pointed to operational deficiencies, equipment issues, and workplace conditions. Supervisors emphasized human behavior, psychological stress, and a lack of safety culture, while safety officers highlighted managerial weaknesses and inefficient communication structures. The quantitative phase results identified management as the primary and most influential factor, whereas other factors, including humans, machinery, environment, and materials, predominantly appeared as dependent factors. This study’s findings suggest that understanding and analyzing the causal relationships among factors, coupled with integrating diverse perspectives, can aid in designing effective preventive strategies and reducing mining accidents. This approach enhances safety, productivity, and job satisfaction.